Gene Interactions Regulating Sex Determination in Cucurbits - Li, Dandan; Sheng, Yunyan; Niu, Huanhuan; Li, Zheng (Frontiers in Plant Science, 2019)
The family Cucurbitaceae includes many economically important crops, such as cucumber (Cucumis sativus), melon (Cucumis melo), watermelon (Citrullus lanatus), and zucchini (Cucurbita pepo), which share homologous gene pathways that control similar phenotypes. Sex determination is a research hotspot associated with yield and quality, and the genes involved are highly orthologous and conserved in cucurbits. In the field, six normal sex-types have been categorized according to the distribution of female, male, or bisexual flowers in a given plant. To date, five orthologous genes involved in sex determination have been cloned, and their various combinations and expression patterns can explain all the identified sex-types. In addition to genetic mechanisms, ethylene controls sex expression in this family. Two ethylene signaling components have been identified recently, which will help us to explore the ethylene signaling-mediated interactions among sex-related genes. This review discusses recent advances relating to the mechanism of sex determination in cucurbits, and the prospects for research in this area.